Sulfonic Acid Functionalized Chitosan as a Sustainable Component for Proton Conductivity Management in PEMs. Issue 8 (14th March 2017) - Ressam, Ibtissam; Krins, Natacha; Laberty‐Robert, Christel; Selmane, Mohamed; Lahcini, Mohammed; Raihane, Mustapha; Kadib, Abdelkrim El; Perrot, Hubert; Sel, Ozlem
Abstract: One of the most fundamental assets of natural polysaccharides is their water storage capacity. Analogically, materials able to regulate water hydration in energetic systems (e.x.: fuel‐cells) are of paramount interest. In light of this key characteristic, chitosan, an aminocarbohydrate derived from shellfish waste, was structurally conjugated using sulfosuccinic acid to afford CS‐SO3 H. The resulting polymeric material appears well suitable for enhancing proton conduction and tuning the hydrophilic‐hydrophobic balance of the proton exchange membranes (PEM). Consequently, Nafion membrane modified with CS‐SO3 H presented σH + values almost 2 times higher than that of pristine Nafion at every % RH level exposed (30 °C ‐ 80 °C and 30% ‐ 90%). The σH + enhancement is in agreement with the lower activation energy indicating that the proton transport is facilitated in the presence of ‐SO3 H modified chitosan. We have found indications that –SO3 H modified chitosan polymer, as a sustainable additive to Nafion is able to control the proton conduction mechanism and keep the activation energy for proton conduction at lower values as compared to pristine Nafion. Abstract : Nafion membranes modified with CS‐SO3 H present protonic conductivity values almost 2 times higher than that of pristine Nafion. The σH + enhancement is in agreement with the lower activation energy indicating that the proton transport is facilitated in the presence of ‐SO3 H modified chitosan, probably due to an alteration of the dominant proton conduction mechanism.